Smart authoring and sharing of multimedia content in personal area networks based on Subject of Interest - Abu-Naim, Belal; Klas, Wolfgang (Proceedings (IEEE International Conference on Multimedia and Expo), 2014)
The evolution of smart phones' hardware and operating systems, users tendency to join social networks and to share multimedia content and daily life events, well-established methods and technologies of Semantic web, and the increasing establishment of Linked Open Data (LOD) APIs, motivate us to introduce a new approach in multimedia content composition and sharing in personal area networks that automatically analyzes, selects, composes, and shares the authored content. The capabilities of social network applications and the applications that address multimedia document composition, retrieval and presentation, and multimedia content sharing, do not go beyond allowing the users to share text, pictures, or other types of media content in social networks, performing manual or semi-automatic multimedia document composition, retrieving a list of pre-composed multimedia documents that eventually include datasets retrieved from DBpedia based on the geographic location. There is a lack of applications that are capable to automatically analyze the multimedia content on the devices of the users, compose multimedia documents about the Subject of Interest (SOI), retrieve and use additional data from LOD sources, and achieve a cross-multimedia document models authoring. In this paper we introduce our innovative approach of automatic analysis, composition, and sharing of multimedia content driven by a user's subject of interest (SOI). Our new approach enables us to achieve a smart multimedia authoring and sharing by incorporating new phases within the authoring process, which have not yet been applied by other applications.